Comparative for the EWMA charts by using non - homogeneous markov chain approach - Naser, J.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this study, we investigate the run length properties for the EWMA charts with time - varying control limits, and fast initial Response (FIR), for monitoring the mean of a normal process with a known standard deviation , by using non - homogeneous markov chain approach.